Subchondral bone dysplasia mediates susceptibility to osteoarthritis in female adult offspring rats induced by prenatal caffeine exposure. (15th March 2020) - Xie, Xingkui; Tan, Yang; Xiao, Hao; Wen, Yinxian; Magdalou, Jacques; Chen, Liaobin; Wang, Hui
Highlights: Prenatal caffeine exposure inhibited subchondral bone development. Prenatal caffeine exposure reduced subchondral bone mass consistently. Prenatal caffeine exposure then induced offspring's susceptibility to osteoarthritis. Abstract: Our previous studies confirmed that prenatal caffeine exposure (PCE) could induce susceptibility to osteoarthritis in adult offspring rats due to poor chondrocyte differentiation, but its mechanism remains to be further investigated. This study aimed to explore whether subchondral bone dysplasia mediates susceptibility to osteoarthritis in adult offspring rats induced by PCE. Pregnant Wistar rats were treated with caffeine (120 mg/kg.d) or saline from gestational day (GD) 9 to 20. The female offspring were euthanized to collect femurs at GD20, postnatal week (PW) 6, and PW28 (non-ovariectomy and ovariectomy groups) to detect osteoarthritis-like phenotype, subchondral bone mass, ossification center development, and other evidence. The results showed that PCE increased the Mankin score of pathological articular cartilage, but decreased articular cartilage thickness and subchondral bone mass, which were more obvious after ovariectomy. Meanwhile, the correlation analysis results demonstrated that the Mankin score of articular cartilage was significantly negatively correlated with subchondral bone mass, and the thickness of articular cartilage was significantly positively correlated with subchondral bone mass. Further, the length and area of the primary and secondary ossification centers, the number of osteoblasts, and the related genes' expression of osteogenic differentiation (e.g., Runx2, BSP, ALP, and OCN) were all significantly decreased in the PCE group before and after birth. Taken together, PCE induced susceptibility to osteoarthritis in adult female offspring, which was likely related to the subchondral bone dysplasia and reduction of subchondral bone mass production due to developmental disorder of primary and secondary ossification centers caused by osteoblast differentiation disability before and after birth.